Implementation of Research and Development Based on Patent Natural Ingredients and Potential Utilization of Tradition Medicine - Hendrix, Tommy (The Asian Journal of Technology Management (AJTM), 2016)
Abstract. The results of research and development based on natural ingredients for traditional medicines become an interesting topic to discuss at this point; itâ€™s shown from increasing number in utilization. The use of traditional medicine especially on natural ingredients at this moment becomes effective solution to increase the level of market acceptance in herbal extracts, including an affordable purchase from potential utilization of natural resources which are owned. By using Matheo Patent XE Ver 10.2 as methodology of searching, we can know potentials useful through strategy, research and development, patent analysis and patent collaboration among users in utilization of Natural Ingredient for Traditional Medicine. From the data result shows majority in the field of chemistry for human necessity related to Health; Amusement; Medical or Veterinary Science; Hygiene sectors with total patent 108, family 65. The use of patent analysis is a way to find how the development of technology and products that have been produced and how commercial processes connecting with technology users, especially in traditional medicine. From the data that exist in particular of patents, it is critical to identify the number of patents that has been registered through the innovation process development including technology dissemination is used. Keywords: Â Implementation, Matheo Patent XE Ver. 10.2, Natural Ingredients, Potential Utilization, Traditional Medicine.